Hypotensive effect of tenuifolic saponin and its mechanism - Peng Wen-duo (Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of tenuifolic saponin (TS) on arterial pressure. METHODS: Mean arterial pressure (MAP) was recorded from left carotid artery in rat which was anesthetized with urethane and then injected i.v. gtt with a transfusion of NaCl 0.15 mol.L-1. Systolic blood pressure (SBP) of conscious rat and renovascular hypertensive rat (RVHR) was measured by tail cuff method. RESULTS: TS 2, 4, 8 mg.kg-1 i.v., 20 and 40 mg.kg-1 i.g. reduced the MAP by 31%, 37%, 50%, 21%, and 31%, respectively. Bilateral vagotomy plus atropine (Atr) i.v., or pretreatment with diphenhydramine hydrochloride (Dip) failed to influence TS effect. Lack of effect of TS on carotid-occlusion-induced- or epinephrine (Epi)-induced-hypertensive response was found. SBP in conscious rat and RVHR was suppressed, highest by 38.0% and 26.8% at 60 and 90 min, maintaining at least 2 and 3 h, respectively, after i.g. TS 40 mg.kg-1. CONCLUSION: TS reduced the arterial pressure, not related to vagus excitation, ganglionic blockade, and peripheral alpha-adrenergic-, M-cholinergic-, and H1-receptors.